Structure, electrical conductivity, and Raman spectra of (Cu1–xAgx)7GeS5I and (Cu1–xAgx)7GeSe5I mixed crystals - Studenyak Ihor; Студеняк Ігор; Pogodin Artem; Погодін Артем; Viktor Studenyak; Студеняк Віктор; Filep Mykhailo; Філеп Михайло; Filep Mihály; Oleksandr Kokhan; Кохан Олександр; Peter Kus; et al. (My University, 2021)
Abstract. The structure of (Cu1–xAgx)7GeSe5I mixed crystals with Cu+↔Ag+substitution is described and compared to (Cu1–xAgx)7GeS5I employing the results of X-ray diffraction (XRD) and the atomic coordinates by Rietveld refinement. Based on the electrical measurements, the compositional behaviour of ionic and electronic conductivity as well as the ratio of ionic and electronic components of conductivity for (Cu1–xAgx)7GeS5I and (Cu1-xAgx)7GeSe5I is discussed. Raman spectra of (Cu1-xAgx)7GeSe5I and (Cu1-xAgx)7GeSe5I are consistent with the XRD data regarding their cubic structure. A one-mode compositional behaviour of the most prominent peak (corresponding to the vibrations of GeS4 or GeSe4 tetrahedra) under Cu→Ag cation substitution is observed, an unexpectedly strong shift of the peak frequency with x reveals its marked effect on the dynamics of GeS4 or GeSe4 tetrahedra. Compounds with high Ag content undergo photochemical surface transformations under laser irradiation during Raman measurements.
Editorial board: https://www.sciencedirect.com/journal/materials-research-bulletin/about/editorial-board Contents: https://www.sciencedirect.com/journal/materials-research-bulletin/vol/135/suppl/C
Keywords: Mixed crystals; Electrical conductivity; Fast-ion conductors; Raman spectroscopy